2022
DOI: 10.2147/cia.s384612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pudendal Nerve Block on the Prevention of Postoperative Bladder Spasm and Catheter-Related Bladder Discomfort in Male Patients Undergoing Transurethral Holmium Laser Enucleation of the Prostate

Abstract: Purpose Bladder spasm (BS) and catheter-related bladder discomfort (CRBD) are complications after transurethral holmium laser enucleation of the prostate (HoLEP). The pudendal nerve (PN) innervates the perineum. Therefore, we evaluated whether PN block (PNB) can reduce the incidence of BS and CRBD in patients undergoing HoLEP. Methods In this randomized, parallel, single-blind prospective study, we enrolled 110 patients who were scheduled to undergo HoLEP under general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Li Xiaoqiang et al [ 15 ] performed PNB to reduce CRBD in TURP cases and compared it with the control group and found that the incidence of CRBD was 52% to 64% in the pudendal group and 69% to 90% in the control group and was statistically significant at all times. Wang SY [ 16 ] found that VAS scores, incidence, and severity of CRBD decreased with PNB use in Holep surgery. The incidence was found to be 3.6–36.4% in the PNB group and 38.2–76.4% in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Li Xiaoqiang et al [ 15 ] performed PNB to reduce CRBD in TURP cases and compared it with the control group and found that the incidence of CRBD was 52% to 64% in the pudendal group and 69% to 90% in the control group and was statistically significant at all times. Wang SY [ 16 ] found that VAS scores, incidence, and severity of CRBD decreased with PNB use in Holep surgery. The incidence was found to be 3.6–36.4% in the PNB group and 38.2–76.4% in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Data from a similar study by Wang SY et al [ 16 ] investigating the difference in the incidence of CRBD between transholium laser therapy pudendal block and control groups were used to determine the sample size. The minimum number of patients to be included in this study was calculated as 24 in each group using G*Power software (latest ver.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations